Effects of Closed Endotracheal Suctioning on Systemic and Cerebral Oxygenation and Hemodynamics in Children. Issue 1 (January 2018) - Chegondi, Madhuradhar; Francis, Teshaun; Lin, Wei-Chiang; Naqvi, Sayed; Raszynski, Andre; Totapally, Balagangadhar R.
Abstract : Objectives: To evaluate the effects of closed endotracheal tube suctioning on systemic oxygen saturation, cerebral regional oxygen saturation, and somatic regional (renal) oxygen saturation and hemodynamic variables in children. Design: Prospective observational. Setting: A tertiary care PICU. Subjects: Children aged 0-18 years, requiring invasive mechanical ventilation and with an arterial line. Interventions: Closed endotracheal suction. Measurements and Main Results: The study included 19 sedated and intubated children, 0–18 years old. They were enrolled in an ongoing prospective observational study. We used near-infrared spectroscopy for cerebral regional oxygen saturation and somatic regional (renal) oxygen saturation. The timing of each closed endotracheal tube suctioning event was accurately identified from video recordings. We extracted systemic oxygen saturation, cerebral regional oxygen saturation, somatic regional (renal) oxygen saturation, heart rate, and systolic blood pressure and diastolic blood pressure for 5 minutes before and 5 minutes after each event and used these data for analysis. One-minute average values of these variables were used for repeated-measures analysis. We analyzed 287 endotracheal tube suctioning episodes in 19 children. Saline was instilled into the endotracheal tube during 61 episodes. The mean heart rate (107.0 ± 18.7 vs 110.2 ± 10.4; p < 0.05), mean arterial blood pressure (81.5 ± 16.1 vs 83.0 ± 15.6 mm Hg; p < 0.05), and the mean cerebral regional oxygen saturation (64.8 ± 8.3 vs 65.8 ± 8.3; p < 0.05) were increased after suctioning. The mean systemic oxygen saturation (96.9 ± 2.7 vs 96.7 ± 2.7; p = 0.013) was decreased, whereas the mean somatic regional (renal) oxygen saturation was not significantly different after endotracheal tube suctioning. Repeated-measures analysis revealed transient increases in heart rate, respiratory rate, systolic blood pressure, and diastolic blood pressure; a sustained increase in cerebral regional oxygen saturation; and transient decreases in systemic oxygen saturation and somatic regional (renal) oxygen saturation. Saline instillation did not affect oxygenation or hemodynamic variables. Conclusions: Closed endotracheal tube suctioning in sedated children is associated with transient but clinically insignificant changes in heart rate, blood pressure, cerebral regional oxygen saturation, systemic oxygen saturation, and somatic regional (renal) oxygen saturation. Saline instillation during endotracheal tube suctioning had no adverse effects on systemic or cerebral oxygenation.